2015
DOI: 10.1152/ajpendo.00161.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between branched-chain amino acids and hepatic mitochondria is compromised in nonalcoholic fatty liver disease

Abstract: Elevated plasma branched-chain amino acids (BCAA) in the setting of insulin resistance have been relevant in predicting type 2 diabetes mellitus (T2DM) onset, but their role in the etiology of hepatic insulin resistance remains uncertain. We determined the link between BCAA and dysfunctional hepatic tricarboxylic acid (TCA) cycle, which is a central feature of hepatic insulin resistance and nonalcoholic fatty liver disease (NAFLD). Plasma metabolites under basal fasting and euglycemic hyperinsulinemic clamps (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
88
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 48 publications
7
88
0
Order By: Relevance
“…Notwithstanding the importance of lipid measures in the metabolic syndrome and their potential role in the pathogenesis of fatty liver, many biomarkers in other metabolic pathways were also strongly linked with the risk for fatty liver. Circulating levels of branched‐chain and aromatic amino acids were strongly directly associated with the presence of fatty liver as well as its future risk, confirming previous small cross‐sectional studies . Deviating levels of these amino acids have been considered to be attributable to dysfunctional mitochondrial energy metabolism, adiposity, and insulin resistance and have been associated with the risk for the development of type 2 diabetes in multiple studies .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Notwithstanding the importance of lipid measures in the metabolic syndrome and their potential role in the pathogenesis of fatty liver, many biomarkers in other metabolic pathways were also strongly linked with the risk for fatty liver. Circulating levels of branched‐chain and aromatic amino acids were strongly directly associated with the presence of fatty liver as well as its future risk, confirming previous small cross‐sectional studies . Deviating levels of these amino acids have been considered to be attributable to dysfunctional mitochondrial energy metabolism, adiposity, and insulin resistance and have been associated with the risk for the development of type 2 diabetes in multiple studies .…”
Section: Discussionsupporting
confidence: 76%
“…Circulating levels of branched-chain and aromatic amino acids were strongly directly associated with the presence of fatty liver as well as its future risk, confirming previous small crosssectional studies. (32)(33)(34) Deviating levels of these amino acids have been considered to be attributable to dysfunctional mitochondrial energy metabolism, adiposity, and insulin resistance and have been associated with the risk for the development of type 2 diabetes in multiple studies. (22,23,33,(35)(36)(37) Prospective studies have suggested that aberrations in the dispositions of branched-chain and aromatic amino acids precede insulin resistance, (35) and here we extend these findings by revealing the predictive associations with the 10year risk for fatty liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed metabolic analyses in NAFLD does indicate certain similarities with our model, including the effects on the TCA cycle [49,50]. The effect of fenofibrate in increasing the longchain acylcarnitines in our model is intriguing.…”
Section: Discussionmentioning
confidence: 63%
“…(11) For example, it has been hypothesized that BCAAs might increase Hep-IR through mammalian target of rapamycin signaling. (8,10,15) However, because during fasting most circulating AAs derive from muscle catabolism, (16) which is increased in IR states, it is likely that an alteration in AA concentrations reflects IR rather than the presence of NAFLD. Most previous studies involved mainly subjects with obesity and IR, where AA catabolism is up-regulated, and thus it is not easy to establish if increased fasting concentrations of AAs are related to NAFLD or to peripheral IR.…”
mentioning
confidence: 99%